2021
DOI: 10.1108/ijshe-06-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in higher education: what is happening in Pakistan?

Abstract: Purpose Sustainability in higher education has gained the attention of researchers and academia; however, there is still a need to explore and assess it from different perspectives that are unexplored. This study aims to evaluate and report sustainability and sustainable development in the higher education sector of Pakistan. Design/methodology/approach There are 195 recognized and registered degree awarding institutes in Pakistan. A survey-based study was designed using self-administered questionnaires dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
(58 reference statements)
1
17
0
1
Order By: Relevance
“…But any integration could not be done without SDbased strategic planning by HEI on curriculum revision. This is a similar effort required as reported in a higher education context (Ariffin & Foo, 2020;Habib, Khalil, Khan, & Zahid, 2021;Filho et al, 2021;Wu & Shen, 2016;Lai & Peng, 2020). However, we found that the readiness of participants for integration does not match with the current curriculum.…”
Section: Discussionsupporting
confidence: 69%
“…But any integration could not be done without SDbased strategic planning by HEI on curriculum revision. This is a similar effort required as reported in a higher education context (Ariffin & Foo, 2020;Habib, Khalil, Khan, & Zahid, 2021;Filho et al, 2021;Wu & Shen, 2016;Lai & Peng, 2020). However, we found that the readiness of participants for integration does not match with the current curriculum.…”
Section: Discussionsupporting
confidence: 69%
“…That is, at present, a small stream of research (featured in this manuscript's sample) that contextualizes knowledge in the current climate of reinterpreting pre-pandemic literature. In parallel, there is an increasing volume of sustainability research that is COVID-19 blind [50][51][52][53][54]. To elaborate, papers in the category of COVID-19 blind were published during the pandemic without reference to said pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the concept of sustainable HR is regarded as an inseparable part of an organization’s macro strategy [ 38 ]. Moreover, universities should seek sustainable development so that they can enhance sustainable behaviors among employees and students as well as moderate and decrease the operating effects on the environment [ 39 , 40 ]. This discussion leads to the following hypothesis:…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%